Emotional Reactions to Unequal Payment: The Impact of Meritocratic Ideology and Salary Negotiability - Maitner, Angela (2015)
People respond to low-status inequality with feelings of anger and shame. This work investigates the impact of meritocracy beliefs and implied salary negotiability on individuals’ emotional reactions within a stable status hierarchy. When an unequal system appears negotiable, believing that hard work pays off may decrease anger felt in response to inequality. However, learning that a system is non-negotiable violates expectations associated with meritocratic beliefs, and may therefore increase negative emotion. In two experiments investigating participants’ emotional reactions to payment systems, the more participants endorsed meritocratic ideologies, the less anger they felt when unequal treatment appeared negotiable. Experiment 2 showed that endorsement of meritocracy beliefs increased negative emotions when individuals learned that the unequal payment was non-negotiable. Taken together, this work suggests that it is important to consider beliefs about individual agency alongside system parameters establishing opportunities for individual mobility to understand emotional reactions to unequal treatment.